Characteristics, pathogenic mechanism, zoonotic potential, drug resistance, and prevention of avian pathogenic Escherichia coli (APEC) - Hu, Jiangang; Afayibo, Dossêh Jean Apôtre; Zhang, Beibei; Zhu, Hong; Yao, Lan; Guo, Weiqi; Wang, Xinyu; Wang, Zhiyang; Wang, Di; Peng, Haoheng; Tian, Mingxing; Qi, Jingjing; et al. (Frontiers in Microbiology, 2022)
Although most Escherichia coli (E. coli) strains are commensal and abundant, certain pathogenic strains cause severe diseases from gastroenteritis to extraintestinal infections. Extraintestinal pathogenic E. coli (ExPEC) contains newborn meningitis E. coli (NMEC), uropathogenic E. coli (UPEC), avian pathogenic E. coli (APEC), and septicemic E. coli (SEPEC) based on their original host and clinical symptom. APEC is a heterogeneous group derived from human ExPEC. APEC causes severe respiratory and systemic diseases in a variety of avian, threatening the poultry industries, food security, and avian welfare worldwide. APEC has many serotypes，and it is widespread pathogenic bacterium in poultry. In addition, ExPEC strains share significant genetic similarities and similar pathogenic mechanisms, indicating that APEC potentially serves as a reservoir of virulence and resistance genes for human ExPEC, and the virulence and resistance genes can be transferred to humans through food animals. Due to economic losses, drug resistance, and zoonotic potential, APEC has attracted heightened awareness. Various virulence factors and resistance genes involved in APEC pathogenesis and drug resistance have been identified. Here, we review the characteristics, epidemiology, pathogenic mechanism zoonotic potential, drug resistance of APEC, summarize the current status of diagnosis, alternative control measures, and vaccine development, which may help to better understanding of the pathogenesis and resistance of APEC, thereby reducing economic losses and preventing the spread of multidrug-resistant APEC to humans.